Distributed adaptive control for multiple nonholonomic systems with nonlinearly parameterized uncertainties. (22nd March 2019) - Gu, Jianzhong; Li, Wuquan; Yang, Hongyong
Summary: This paper investigates the distributed adaptive control problem for multiple nonholonomic systems with nonlinearly parameterized uncertainties. Under the assumption that the graph topology is directed and the leader is globally reachable, distributed adaptive controllers are designed recursively by using backstepping technique and algebra graph theory. It is shown that all the followers' outputs will exponentially converge to the reference output signal while all the signals of the closed‐loop system are bounded. Finally, two simulation examples are given to demonstrate the effectiveness of the control scheme.